2018
DOI: 10.1159/000486863
|View full text |Cite
|
Sign up to set email alerts
|

Optic Nerve Haemangioblastoma: Signs of Chronicity

Abstract: Optic nerve haemangioblastomas remain exceedingly rare extrinsic tumours of the optic nerve, often associated with von Hippel-Lindau disease. The authors report a 25-year-old female with a slowly progressive unilateral optic nerve lesion, causing reduced vision and bilateral optic tract oedema. A diagnosis of optic nerve haemangioblastoma with piloid gliosis was made histologically after surgical resection. This is the first reported case of such dual pathology occurring in the optic nerve. The patient has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 19 publications
0
24
1
Order By: Relevance
“…5,14 A more contemporary finding associated with cerebral and optic nerve hemangioblastomas is peritumoral edema. 3,24,38 As retrobulbar hemangioblastomas are often supplied by branches of the ophthalmic artery, the high blood volume and permeability of these tumors results in a disproportionately large amount of edema for the size of the lesion. 25 This edema tends to propagate along low-resistance white matter pathways, and can be demonstrated on serial imaging.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations
“…5,14 A more contemporary finding associated with cerebral and optic nerve hemangioblastomas is peritumoral edema. 3,24,38 As retrobulbar hemangioblastomas are often supplied by branches of the ophthalmic artery, the high blood volume and permeability of these tumors results in a disproportionately large amount of edema for the size of the lesion. 25 This edema tends to propagate along low-resistance white matter pathways, and can be demonstrated on serial imaging.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…7 A recent report by McGrath and coauthors demonstrated Rosenthal fibers with surrounding piloid gliosis in an ONH as a marker for chronicity. 24 Gliosis can accompany neural lesions, with a subset of astrocytic gliosis characterized by elongated, granular, hypereosinophilic, deposits called Rosenthal fibers (Figure 3c). 24 This appearance can be termed 'piloid gliosis', given that it mimics features seen in pilocytic astrocytoma.…”
Section: Macroscopic and Histological Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Beyond the CNS, hemangioblastomas can also occur in the peripheral nervous system [7,8], retroperitoneum [9,10], pelvic cavity [11], soft tissue [12], bone [13], adrenal glands [14], lung, and liver [15].…”
Section: Introductionmentioning
confidence: 99%